ANALYSIS OF THE MULTISECTORAL PLAN FOR THE FIGHT AGAINST ANEMIA IN PERU: AN EXAMPLE OF CHANGE MANAGEMENT - Vasquez-Velasquez, Cinthya (2024)
The Multisectoral Plan for the fight against anemia is a policy document implemented over the period 2018-2020, which involved 15 ministries that make up the Peruvian government. This manuscript performs an analysis based on the phases of change management proposed by Hayes.